Cognitive function in Post-Traumatic Stress Disorder - Kolfinna Þórisdóttir 1995- (2018)
Post-traumatic stress disorder (PTSD) is a psychiatric disorder triggered by a traumatic event involving death, threatened death, actual or threatened serious injury, or actual or threatened sexual violence. Symptoms of PTSD include concentration disturbances in memory along with abnormalities in underlying working memory (WM). The PTSD Checklist from DSM-5 (PCL-5) was completed by 50 students during their second year of BSc study at the Department of Psychology in Reykjavík University, Iceland. There were 13 students who reached the diagnostic criteria for PTSD according to the checklist and 35 who did not. This allowed researchers to compare the two groups on WM and memory tasks. Three tasks were used, Digit Span Subtest of the Wechsler Adult Intelligence Scale (WAIS-IV) and Operation Span were used to assess WM, and Logical Memory subtest of Wechsler Memory Scale as a measure of immediate and delayed memory. Results showed no significant differences between the two groups on the WM tasks. On the other hand, a significant difference was found between the groups on the Logical Memory task. These results indicate that memory is impaired in people with PTSD while WM is intact. These findings are in concordance with studies showing memory impairments in individuals with PTSD. However, they do not support evidence for WM impairments in PTSD patients. Áfallastreituröskun er skilgreind sem viðbrögð í kjölfar erfiðrar lífsreynslu, til dæmis í kjölfar líkamsárásar, nauðgunar eða dauðsfalls. Einkenni felast meðal annars í því að endurupplifa atburðinn á einhvern hátt, auk þess að upplifa svefntruflanir, einbeitingaerfiðleika og að vera ofurviðbrigðin. Til þess að vera greindur með áfallastreituröskun þarf einstaklingur að sýna einkenni áfallastreituröskunar í meira en einn mánuð. Í þessari rannsókn voru 50 nemendur á öðru ári í Sálfræðideild Háskólans í Reykjavík sem svöruðu spurningalista sem metur einkenni áfallastreituröskunar (PTSD Checklist for DSM-5, PCL-5). Það voru 13 nemendur sem uppfylltu ...